A Internet na comunicação em saúde: construindo um site baseado na interatividade. - Soares, Murilo Cesar [UNESP] (My University, 2013)
The paper presents three steps of a study about the Internet use in health communication. The first refers to the potentials and limitations of the web for health initiatives in general. The second provides an assessment of health sites in Brazil dedicated to people who want to quit smoking, performed using a standardized form, indicating strengths and weaknesses of existing sites. The last part of the text, based on these data, concerns the application of a model in stages on the internet, to support smokers who want to quit smoking.

O texto apresenta três fases de uma pesquisa sobre a utilização da Internet na comunicação em saúde. A primeira se refere às potencialidades e limitações da rede para ações de saúde, em geral. A segunda traz uma avaliação de sites de saúde brasileiros dedicados a pessoas que querem parar de fumar, realizada com a utilização de um formulário padronizado, indicando pontos fortes e debilidades dos sites existentes. A última parte do texto, com base nesses dados, se refere à aplicação na internet de um modelo em etapas para mudança de comportamento, visando apoiar fumantes que querem abandonar o cigarro.
Internet in health communication: building a website based on interactivity
Keywords: Health communication; Internet; Interactivity; Quit smoking; Comunicação em saúde; Internet; Interatividade; Deixar de fumar